Protein Identification in Latex Gloves for Bio-compatibility using Maximum Minimal Variation Test - K. S., Sim; F. S., Chin; L. W., Thong (2008)
This paper introduces a method for biocompatibility testing on surgery glove. This new method can avoid bio-implantation and it only requires standard procedure to operate it. The three protein tests, Millon's test, Ninhydrin test and Xanthroproteic test are performed on the samples, and images of samples after going through each test are obtained for image processing. The image processing algorithm developed is Maximum Minimal Variation (MMV), which is able to detect the content of protein in the sample. Tests conducted shows promising results.